Relevant tumor sink effect in prostate cancer patients receiving 177Lu-PSMA-617 radioligand therapy - Filss, Christian; Heinzel, Alexander; Miiller, Berthold; Vogg, Andreas T. J.; Langen, Karl-Josef; Mottaghy, Felix M. (Nuklearmedizin - NuclearMedicine, 2018)
Aim: In metastatic prostate cancer patients PSMA targeting radioligands have gained significant impact as theranostic probes. In this study a correlation between total tumor volume (TTV) and measured kidney dose as well as salivary glands (SG) uptake in 177Lu-PSMA-617 therapy was evaluated.Methods: Eleven consecutive prostate cancer patients receiving a first cylcle of 177Lu-PSMA-617 (administered activity of approximately 6GBq) were included. The 68Ga-PSMA-11 PET/CT scan previous to therapy was used to determine TTV and SG uptake (glandulae submandibularis) employing PMOD version 3.403 with different 68Ga-PSMA-11 thresholds based on the standardized uptake value (SUV).The kidney dose was estimated with the software ULMDOS using planar whole-body scintigrams.Results: Kidney dose and SG uptake was inversely correlated to TTV, indicating high kidney dose and high SG uptake in case of low tumor load and low kidney dose and low SG uptake in case of high tumor load.Conclusion: Our data support the hypothesis that in 177Lu-PSMA-617 therapy an individualized treatment activity based on total tumor volume could be beneficiary.
Keywords: Prostate Cancer; Dosimetry; Therapy; PSMA; Scintigraphy